Plasma Metabolites and Gut Microbiota Are Associated With T cell Imbalance in BALB/c Model of Eosinophilic Asthma - Zhou, Yumei; Wang, Tieshan; Zhao, Xiaoshan; Wang, Ji; Wang, Qi (Frontiers in Pharmacology, 2022)
Regulatory T cells (Treg) and T helper 17 (Th17) cells have an important role in the pathogenesis of allergic asthma. Yet, the exact role of Treg and Th17 cells in eosinophilic asthmatic disease and airway remodeling is not fully understood. This study used an untargeted plasma metabolome to identify new biomarkers of plasma metabolites in ovalbumin-induced eosinophilic allergic asthma in mice. Besides, we also used 16S rDNA technology to analyze gut microbiota and to further explore the role of plasma metabolites in regulating the immune balance or the immune response. We discovered that pro-hyp, 1-behenoyl-2-hydroxy-sn-glycero-3-phosphocholine, 2-denoxy-d-glucose, glutamine, L-ascorbic acid, 1,5-anhydro-d-sorbitol in plasma, and certain gut microbiota (genus Candidatus Arthromitus and genus Helicobacter) were associated with Treg/Th17 balance in the eosinophilic asthma mice model. Our data provide a preliminary basis for drug treatment in eosinophilic asthma.